PHYTOCHEMICAL CONSTITUENT, ACUTE AND SUBACUTE TOXICITY STUDIES OF METHANOL EXTRACT OF LAPORTEA AESTUANS LEAF - Adeosun, Abiola; Akamo, A. J.; Akinloye, O. A.; Shotuyo, A. L. A. (FUDMA JOURNAL OF SCIENCES, 2022)
Laportea aestuans is an African herbaceous weed. This work assessed the bioactive compound content of methanol extract of Laportea aestuans leaf (LALME) and its acute and subacute toxicity effects in Male Wistar rats. According to qualitative and quantitative phytochemical analysis, LALME possesses a significant amount of phenolics, flavonoids, alkaloids, tannin, carotenoids, and anthraquinones. LALME is regarded as safe because it did not cause death in rats when given doses of up to 2,000 mg/kg body weight. LALME at 200 and 400 mg/kg markedly increased (p
Keywords: Bioactive, Phytochemicals, Laportea aestuans, Toxicity Study